The expression of mercaptopyruvate sulfurtransferase serves as a potential biomarker for prognostic stratification and immunotherapy in certain cancers - Cui, Boran; Xia, Chenchen; Yang, Li; Xi, Xiaoyu; Gong, Xinxin; Liu, Yixi; Tian, Cai; Du, Xiaoli; Du, Jiexian; Hao, Zengfang (Frontiers in Oncology, 2026)
Introduction3 - Mercaptopyruvate Sulfurtransferase (3 - MST) is an enzyme encoded by the Mercaptopyruvate Sulfurtransferase (MPST) gene. The enzyme is associated with a variety of cancers such as lung adenocarcinoma. However, there is a lack of comprehensive pan-cancer analysis on the potential impact of MPST on cancer diagnosis, prognosis, and immune response.MethodsBased on data from The Cancer Genome Atlas and the Human Protein Atlas, we conducted a comprehensive bioinformatic analysis to investigate the oncogenic role of MPST. Immune-related characteristics and tumor microenvironment infiltration were assessed using TIMER2.0. Protein-protein interaction networks were constructed via STRING, while DNA methylation differences across cancers were analyzed with UALCAN. Further insights into genetic alterations and functional states at the single-cell level were obtained from cBioPortal and CancerSEA. Finally, clinical samples were collected and subjected to immunohistochemical staining to preliminarily validate the bioinformatic findings.ResultThe research assessed the links between MPST levels and various cancer outcomes, genetic alterations, immune cell presence, and DNA methylation patterns. Single-cell sequencing was utilized to deepen our comprehension of its functional importance. Furthermore, the unique immunohistochemical profiling of MPST in patient tissue was confirmed. Significant expression differences between tumors and normal tissues in certain cancer types suggest a correlation between MPST expression and clinical outcomes. Furthermore, correlations exist between MPST expression levels in different immune cells and the tumor immune microenvironment. Our observations also indicate a role for MPST methylation, along with the advantageous effects of highly amplified mutations and deletions of the MPST gene.DiscussionSignificantly, MPST shows potential for early cancer identification and as a predictive factor for various tumor forms.